Chapter La disuguaglianza economica in area marchigiana: uno studio di lungo periodo (1400-1800) - Ammannati, Francesco (Datini Studies in Economic History, 2020)
The research aimed at bringing new data to the study of inequality in the distribution of wealth in the long run using the fiscal documentation available to many communities of the Marches region over a period covering the late Middle Ages and the full modern age. The political-administrative history of this territory, progressively incorporated into the Papal State, was reflected in an evolution of the methodologies for assessing wealth for tax purposes. Their characteristics have been carefully taken into account and criticized in order to ensure compatibility in time and space. Land registers, "estimi", "libre", as well as books of "collette", will be used to describe the fiscal capacity of taxpayers enrolled in these registers and to estimate the dynamics of economic inequality.